Hubungan Dukungan Keluarga terhadap Kepatuhan Minum Obat Penderita Tuberculosis Paru di Wilayah Kerja UPTD Puskesmas Kuta Selatan - Made Diah Padmawati; Luh Gede Pradnyawati; Dewa Ayu Putu Ratna Juwita (Aesculapius Medical Journal, 2024)
[The Relation between Family Support and Pulmonary Tuberculosis Drugs Compliance in Working Area of UPTD Puskesmas Kuta Selatan]. The high number of cases of pulmonary tuberculosis and the low success rate of treatment (success rate) caused by non-compliance with recommendations for taking medication can result in sufferers experiencing drug resistance. Family support is needed to ensure that sufferers take medication because the tuberculosis treatment process takes a long time so that the drug withdrawal rate can be reduced. The purpose of this research is to find out the family relationship to compliance with drug consumption in pulmonary tuberculosis victims in the working area of UPTD Puskesmas Kuta Selaran??. A cross-sectional design was used on 35 respondents using a sampling technique using consecutive sampling. Information was collected through the use of 2 types instruments, namely family support questionnaires and the Morisky Medication Adherence Scale-8 (MMAS-8) regarding adherence. The data collected was analyzed using univariate analysis and bivariate analysis using the chi square test. The results obtained that there was a relations between family support and drug compliance (? value=0.015, <0.05) and people through good family support are 9,500 times more compliant in taking medication than those with less support. Researchers recommend that health workers carry out outreach to increase family support with the target which not only affects the sufferer but also the family.